2018
DOI: 10.1111/1365-2435.13232
|View full text |Cite
|
Sign up to set email alerts
|

Why are plant–soil feedbacks so unpredictable, and what to do about it?

Abstract: The study of feedbacks between plants and soils (plant–soil feedbacks; PSFs) is receiving increased attention. However, PSFs have been mostly studied in isolation of abiotic and biotic drivers that could affect their strength and direction. This is problematic because it has led to limited predictive power of PSFs in “the real world,” leaving large knowledge gaps in our ability to predict how PSFs contribute to ecosystem processes and functions. Here, we present a synthetic framework to elucidate how abiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 80 publications
(124 reference statements)
3
91
0
Order By: Relevance
“…Our study revealed that among the abiotic factors temperature was the most important for biotic elements, which reflects its immense significance in physical constraints for arctic biota 1 and the general tendency of modifying interactions between organisms 57 . However, our results also suggest that the impact of temperature on an arctic host plant is far more complex than previously thought 58,59 and in general, perhaps unpredictable 60 . The mechanism behind fungal mediation of temperature is not clear.…”
Section: Discussionsupporting
confidence: 54%
“…Our study revealed that among the abiotic factors temperature was the most important for biotic elements, which reflects its immense significance in physical constraints for arctic biota 1 and the general tendency of modifying interactions between organisms 57 . However, our results also suggest that the impact of temperature on an arctic host plant is far more complex than previously thought 58,59 and in general, perhaps unpredictable 60 . The mechanism behind fungal mediation of temperature is not clear.…”
Section: Discussionsupporting
confidence: 54%
“…These results are in contrast with previous results of van Grunsven et al (2010), in which direction of PSF detected between pairs of European congeners was largely unaffected by variation in testing temperature, though this study did not manipulate temperature in the testing environment. Our results suggest that across year variation in climate may be one reason why plant-soil feedbacks have been observed to be variable (De Long et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…The first mechanism is that the changes in the AM fungal community contributed to the negative PSF observed (Bever, 2002). In the event of elevated temperatures, AM fungi may decrease activity (Mohan et al, 2014), which in turn weakens positive PSF (De Long et al, 2019), which could further explain our observed negative feedbacks. Changes to the fungal community were likely more pronounced due to the greater growth of the non-native grass relative to the native grass in the training phase of the experiment (Duell et al, 2016) under elevated temperatures (Supplementary Tables 4-6; Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 85%
“…Although above-belowground biotic interactions have a strong potential to aid sustainable agriculture, the ecological context in which they operate varies strongly across the globe and this can alter how they drive crop growth and ecosystem functioning (Agrawal et al, 2007;Pittelkow et al, 2015;Karp et al, 2018; Figure 2). The impact of soil legacies on plants is strongly dependent on climatic conditions (De Long et al, 2018), as well as biotic and abiotic environmental conditions Casper and Castelli, 2007;Ke et al, 2015). For example, the magnitude and direction of plant growth responses to soil legacy effects can be modified by soil texture or chemistry .…”
Section: Environmental Contextmentioning
confidence: 99%